2003
DOI: 10.1091/mbc.e02-08-0511
|View full text |Cite
|
Sign up to set email alerts
|

Pre-M Phase-promoting Factor Associates with Annulate Lamellae inXenopusOocytes and Egg Extracts

Abstract: We have used complementary biochemical and in vivo approaches to study the compartmentalization of M phase-promoting factor (MPF) in prophase Xenopus eggs and oocytes. We first examined the distribution of MPF (Cdc2/CyclinB2) and membranous organelles in high-speed extracts of Xenopus eggs made during mitotic prophase. These extracts were found to lack mitochondria, Golgi membranes, and most endoplasmic reticulum (ER) but to contain the bulk of the pre-MPF pool. This pre-MPF could be pelleted by further centri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
19
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 85 publications
6
19
0
Order By: Relevance
“…The agreement of the three methods provides strong evidence that a significant fraction of the inactive Cdc2-cyclin B is not freely soluble in the cytoplasm and that at least some of this fraction is released at the activation. Our results are similar to those of Westendorf et al (1989) who described cyclin B aggregates in clam oocytes that disperse on oocyte activation, and to Beckhelling et al (2003) who found an association of Cdc2-cyclin B with annulate lamellae in frog oocytes that disperses during oocyte maturation.There are several important unresolved issues. The composition of the aggregates in starfish oocytes is not known.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…The agreement of the three methods provides strong evidence that a significant fraction of the inactive Cdc2-cyclin B is not freely soluble in the cytoplasm and that at least some of this fraction is released at the activation. Our results are similar to those of Westendorf et al (1989) who described cyclin B aggregates in clam oocytes that disperse on oocyte activation, and to Beckhelling et al (2003) who found an association of Cdc2-cyclin B with annulate lamellae in frog oocytes that disperses during oocyte maturation.There are several important unresolved issues. The composition of the aggregates in starfish oocytes is not known.…”
supporting
confidence: 91%
“…When the Golgi apparatus was localized by galtransferase-GFP expression, it also shows as spots scattered throughout the cytoplasm (Terasaki, 2000), but double staining by cyclin B immunofluorescence showed that the Golgi apparatus and spots were not colocalized (our unpublished data). Cyclin B is not associated with annulate lamellae as in Xenopus oocytes (Beckhelling et al, 2003) because starfish oocytes do not possess annulate lamellae by electron microscopy or by immunofluorescence labeling (our unpublished data).…”
Section: Cyclin B Is Present In Aggregates In Immature Oocytes and DImentioning
confidence: 82%
See 2 more Smart Citations
“…One possibility is that, despite the reported excess of cyclin B, much of it may be sequestered , de Vantéry et al 1997, Beckhelling et al 2003. A small increase in 'free' exogenous cyclin B1 may provide a sufficient increase in pre-MPF available for cdc25 to initiate the auto-catalytic reaction leading to complete MPF activation (Hoffmann et al 1993, Lincoln et al 2002.…”
Section: Exogenous Cyclin Stimulates Progression Through Meiosismentioning
confidence: 99%